854Predictors of ventricular tachyarrhythmia in patients with implantable cardioverter-defibrillator and non-ischaemic systolic heart failure. (18th June 2020) - Jedrzejczyk-Patej, E; Mazurek, M; Lazar, M; Pruszkowska-Skrzep, P; Podolecki, T; Kowalczyk, J; Kowalski, O; Kalarus, Z; Lenarczyk, R
Abstract: Funding Acknowledgements: none OnBehalf: none Background: The benefit of an implantable cardioverter-defibrillator (ICD) in patients with ischaemic heart failure (HF) has been well proven but the benefit of ICD in subjects with non-ischaemic systolic HF is less well-established. Consequently, there is very limited evidence which patients with non-ischaemic HF would benefit most from receiving an ICD. Aim To determine the incidence and predictors of ventricular arrhythmia in patients with ICD and non-ischaemic systolic HF. Methods: Study population consisted of 420 consecutive patients with ICD and non-ischaemic systolic HF monitored remotely (on a daily basis) between 2010 and 2017 in tertiary care university hospital, in a densely inhabited, urban region of Poland. Sixty-six percentage of patients had cardiac resynchronization therapy with defibrillator (CRT-D). Results: During the median follow-up of 1645 days (range: 507-3515) sustained ventricular arrhythmia occurred in 100 patients (23.8%). Of those, ventricular fibrillation (VF), ventricular tachycardia (VT) or VT/VF (combined) occurred in 10 (10.0%), 77 (77.0%) and 13 (13.0%) patients, respectively. Patients with versus without ventricular arrhythmia did differ with respect to baseline variables such as: left ventricular end diastolic diameter (LVEDD) - median of 67 mm [49-82] vs 62 mm [46-78]; post-inflammatory HF (17 vs 9.7%, P = 0.045); atrial fibrillation/atrial flutter - AF/AFL (57 vs. 38.1%, P = 0.0009); supraventricular arrhythmia (SVT) - any supraventricular arrythmia >100/min other than AF/AFL (27 vs. 15.9%, P = 0.01); and left ventricular ejection fraction - EF (25 vs. 28%, P = 0.01). No differences were observed for age, sex, NYHA class, mitral regurgitation, common comorbidities (including diabetes and chronic renal disease) or concomitant medications. On multivariable regression analysis, LVEDD (HR 1.05, 95% CI 1.004-1.09, P = 0.03), AF/AFL (HR 1.81, 95% CI 1.21-2.72, P = 0.004) and SVT (HR 1.91, 95% CI 1.21-3.01, P = 0.006) were identified as independent predictors of sustained ventricular arrhythmia in patients with ICD and non-ischaemic HF. All-cause mortality in patients with VT/VF was significantly higher than in subjects without sustained ventricular arrhythmias (33% vs. 20%, P = 0.03). Conclusions: Ventricular arrhythmia occurred in 23.8% of patients with systolic non-ischaemic HF during 4.5 years of observation and was associated with significantly worse prognosis compared with subjects free of VT/VF. Left ventricular dimension, atrial fibrillation/atrial flutter and supraventricular tachycardia were identified as independent predictors for ventricular arrhythmia.